Science engagement and literacy: a retrospective analysis for students in Canada and Australia - Woods-McConney, Amanda; Oliver, Mary; McConney, Andrew; Schibeci, Renato; Maor, Dorit (Taylor & Francis Group, 2014)
Given international concerns about students’ pursuit (or more correctly, non-pursuit) of courses and careers in science, technology, engineering and mathematics (STEM), this study is about achieving a better understanding of factors related to high school students’ engagement in science. The study builds on previous secondary analyses of Programme for International Student Assessment (PISA) datasets for New Zealand and Australia. For the current study, we repeated these analyses to compare patterns of science engagement and science literacy for male and female students in Canada and Australia. The study’s secondary analysis revealed that for all PISA measures included under the conceptual umbrella of engagement in science (i.e., interest, enjoyment, valuing, self-efficacy, self-concept, and motivation), 15-year-old students in Australia lagged their Canadian counterparts to varying, albeit modest, degrees. Our retrospective analysis further shows, however, that gender equity in science engagement and science literacy is evident in both Canadian and Australian contexts. Additionally, and consistent with previous findings for indigenous and non-indigenous students in New Zealand and Australia, we found that for male and female students in both countries, the factor most strongly associated with variations in engagement in science was the extent to which students participate in science activities outside of school. In contrast, and again for both Canadian and Australian students, the factors most strongly associated with science literacy were students’ socioeconomic backgrounds, and the amount of formal time spent doing science. The implications of these results for science educators and researchers are discussed.